The Impact of an Evidence-Based Bundle on Cesarean Section-Related Surgical Site Infections: A Randomized Clinical Trial - Aditya Gan; Romana Khursheed; Mahadevi Savanur; Anita Dalal; Arif Maldar; Yang Pan; Jue Li (Maternal-Fetal Medicine)
Abstract. Objective. To compare the effectiveness of an evidence-based bundle in minimizing cesarean section (CS)-related surgical site infections (SSIs) with that of standard routine care. Methods. This was a single-center, parallel, and randomized clinical trial conducted at KAHER’s Dr. Prabhakar Kore Charitable Hospital, Belagavi, India, from January 2021 to December 31, 2021. Three hundred twenty women undergoing CS delivery were selected and allocated into two groups (1:1) using simple randomization with fixed allocation. An evidence-based surgical bundle (a combination of more than three perioperative interventions) was used for the intervention group, whereas the control group received routine standard perioperative care. The primary outcome was the incidence of SSI (superficial, deep, and organ or space SSIs) within 6 weeks postpartum in both groups. Categorical and continuous data were analyzed using appropriate statistical tests with a significance threshold set at P < 0.05. Results. In this study, 16 and 17 participants each from the control and intervention groups, respectively, were lost to follow-up, resulting in a total of 144 and 143 study participants included in the respective groups. Twenty-eight (19.4%) and 14 (9.8%) women developed SSI in the control and intervention groups, respectively (P = 0.02). Methicillin-resistant Staphylococcus aureus was the most common cause of SSI in both groups (63.6% (7/11) and 100% (3/3) in the control and intervention groups, respectively). Conclusion. The use of the evidence-based bundle for CS-related SSI prevention effectively decreased the incidence of SSI by half compared to standard routine practice. Implementing the use of this bundle in routine perioperative care will reduce the cost of CS and improve health outcomes in CS. Trial registration. Clinical Trials Registry-India (www.ctri.nic.in). Registration number: CTRI/2020/11/029246.